EVALUASI PROGRAM SEKOLAH UNGGULAN SMAN 2 SANGATTA UTARA KABUPATEN KUTAI TIMUR SUATU MODEL EVALUASI DENGAN PENDEKATAN TUJUAN INDEPENDEN (GOAL FREE EVALUATION) - Rubito; Soeprijanto (Jurnal Evaluasi Pendidikan, 2016)
The Purpuse of this evaluation of school programs featured in SMAN 2 Sangatta Utara using models goal free evaluation model. Superior school is a school that has featured a different program that aims to improve student achievement in the mastery of knowledge and have a national identity. Evaluation focused on superior program set by the school to recognize the positive iimpact that suits the purpose of the program, negative impact outside the program's objectives and positive side effects the program objectives. The Subjects were students of class XI grade, teachers, principals and school supervisors. The research method used is descriptive qualitative. Data collection techniques are observation, interviews, documentation and questionnaires. The results of the evaluation of the school program featured a positive impact with a frequency of 33, the negative impact of the frequency of side effects with the 23 and 59. The frequency of research results and the positive impact of a side impact is greater than the negative impact, indicating that the program has been successful but remained negative impacts arising should be noted and repaired so as not to destabilize the already good program.